Effect of an Educational Intervention Based on the Health Belief Model on the Prevention Behaviors of COVID-19 Among Employee - Abbas Javadi (Beyhagh)
Background and Aims: The health behavior model (HBM) is a model that is suitable for teaching behaviours to prevent disease. This study aimed to assess the impact of an educational intervention based on the HBM on the COVID-19 preventive behaviors of office employees in Zirkooh City. Materials and Methods: In this randomized controlled field trial, 66 office workers in Zirkoh city (Eastern Iran) were examined in 1401. They were randomly divided into two intervention and control groups (33 people in each group). A researcher-made questionnaire was utilized to gather data, which was both validated and reliable. The questionnaires were filled out three times prior, immediately after, and three months after the training. Data were analyzed using SPSS 21 and by two-way analysis of variance, Bonferroni Post Hoc test and independent samples t-test at a significance level of 0.05. Result: According to the findings of the study, the mean scores of perceived sensitivity, perceived severity,perceived benefits, obstacles, self-efficacy, action and performance guidelines regarding preventive behaviors immediately and three months later, in the intervention group were significantly higher than the control group (p<0.05) but there was no significant change in the average knowledge score in the two study groups before, immediately, and three months after the intervention. (p>0.05). Conclusion: HBM-based educational intervention program implementation resulted in favorable attitudes and preventive behaviors towards COVID-19 among office workers. Creating and implementing interventions based on this model is recommended to alter behavior for this purpose.